Evaluation of insecticides and natural products for their efficacy against cardamom thrips (Sciothrips cardamomi Ramk.) (Thysanoptera: Thripidae) in the field - Sharon D’Silva, S Devasahayam,, T K Jacob, C M Senthil Kumar,; R Praveena, S J Ankegowda, H R Ranganath, E S Sujeesh, C N Biju, (Journal of Spices and Aromatic Crops, 2015)
Eleven insecticides and natural products were evaluated in the field at Appangala (Karnataka) for their efficacy against cardamom thrips (Sciothrips cardamomi) for three years. Combined analysis of three years data indicated that all the treatments were significantly effective in reducing the damage caused by thrips on capsules compared to control when sprayed during February-March, March-April, April-May and September and October. Fipronil 0.005% treated plots recorded the lowest percentage of damage (6.5%) that was on par with imidacloprid 0.0089%, thiamethoxam 0.0075% and spinosad 0.0135%. The trials indicated that spinosad can substitute synthetic insecticides for thrips control in cardamom, due to their less adverse effects on the environment.